Dynamic EIT technology for real-time non-invasive monitoring of acute pulmonary embolism: a porcine model experiment - Junyao Li; Mingxu Zhu; Yitong Guo; Weichen Li; Qing He; Yu Wang; Yuxuan Liu; Benyuan Liu; Yang Liu; Weice Wang; Zhenyu Ji; Xuetao Shi (Respiratory Research)
Abstract Background Acute pulmonary embolism represents the third most prevalent cardiovascular pathology, following coronary heart disease and hypertension. Its untreated mortality rate is as high as 20–30%, which represents a significant threat to patient survival. In view of the current lack of real-time monitoring techniques for acute pulmonary embolism, this study primarily investigates the potential of the pulsatility electrical impedance tomography (EIT) technique for the detection and real-time monitoring of acute pulmonary embolism through the collection and imaging of the pulsatile signal of pulmonary blood flow. Methods A before-and-after self-control experiment was conducted on anaesthetised domestic pigs (N = 12, 20.75 ± 2.56 kg). The changes in pulmonary perfusion caused by an acute pulmonary embolism (artificially induced) were monitored in real time using the pulsation method. This enabled the extraction of indicators such as Amplitude, Forward (Negative) Slope, and S ARC , which were used to assess the local pulmonary blood flow perfusion state. Furthermore, the degree of ventilation/perfusion matching in the lungs was evaluated concurrently with the analysis of the pulmonary ventilation area. Subsequently, a control verification was conducted utilising the conventional invasive hypertonic saline (5 ml 10% NaCl) contrast technique. Results The perfusion alterations subsequent to embolism in the pulsatility method are highly concordant with those observed in the hypertonic saline method, as evidenced by the imaging and indicator data. In particular, the perfusion area on the side of the embolism is markedly diminished, and the absolute values of all perfusion indicators are significantly reduced. Among these, Amplitude (P < 0.001) and S ARC (P < 0.001) exhibit the most pronounced alterations. Furthermore, the extracted indicators from regional ventilation demonstrated notable discrepancies, the V/Q match% (P < 0.001) and Dead Space% (P < 0.001) exhibited the most pronounced sensitivity to alterations in acute pulmonary embolism. Subsequently, a control verification was conducted utilising the hypertonic saline method, which revealed a high degree of consistency between the two methods in the detection of acute pulmonary embolism (Kappa = 0.75, P < 0.05). Conclusions The EIT imaging method, which is based on the analysis of blood flow pulsation, has the potential to reflect in real time the changes in pulmonary blood flow that occur before and after an embolism. This provides a new avenue for the non-invasive real-time monitoring of patients with acute pulmonary embolism in a clinical setting.